‫دور ‬‫التكاليف‬ ‫الثابتة‬ في‬ ‫ترشيد‬ ‫القرارات‬ ‫التشغيلية‬ ‫و‬ ‫المالية‬ ‫دراسة ‬‫حالة‬ ‫المؤسسة‬ ‫الوطنية‬ ‫للدهن‬ ‫و‬ ‫مطاحن‬ ‫بلغيث‬ ‫الكبرى‬ - ‬‫لويزة‫ غضا‬‫ي‬‫بية‬; ‬‫هادية‫ باليلية‬ (My University, 2019)
This study aims to explain the importance of the contribution of fixed costs on the rationalization of operational and financial decisions in the economic institution as one of the methods used for the purpose of making decisions. In order to address the problem of the subject and test the hypotheses, this study was conducted on the paint factory in Souk Ahras and the company of Belghith’s Greater Mills in Medaourouche based on the relevant financial documents for the period 2015-2017 and the collection of the data needed for the study (fixed costs, operational leverage, Financial leverage) from the documents and their analysis. This study found that despite the lack of interest of the two institutions in the analysis of fixed costs, it is considered an essential element that helps the institution in rationalizing its decisions. Access to information about fixed costs and their relation to the volume of activity and revenues helps decision makers to make sound and rational decisions, in particular operating decisions related to the use of operational leverage resulting from the use of fixed-cost assets to contribute to profit, and the financial decisions associated with the financial leverage relating to the use of fixed financial costs in order to maximize the impact of changes in profits, where both the operational and financial leverage is an important tool used in planning, monitoring, evaluating performance and helping to take and rationalize decisions .